PENDIDIKAN AGAMA DALAM KULTUR SEKOLAH DEMOKRATIS: POTENSI MEMBUMIKAN DERADIKALISASI AGAMA DI SEKOLAH - Jannet, Herly (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
This study aimed in general to determine and describe the religious education in a democratic school culture is one of potential strategies in disseminating religious de-radicalization in schools. Applying qualitative naturalistic approach with case study, this study focused the location in Christian High School Urimessing Ambon. The object of this research was the all democratic phenomena found in the process of teaching and learning of Christian education. The results of this study can be described as follows: religious education in a democratic school culture has the potential to disseminate de-radicalization because the learning process optimized the attitude of critical thinking on freedom, independence, and accountability that were assumed to build the belief, attitude and norm of student to: (1) deepen and believe their own religious teachings; (2) commit to transform their religious teacgings in their daily life, both individually and socially; and (3) become the real who got off from violence and anarchy in realizing their objectives.***Penelitian ini bertujuan untuk menemukan dan mendeskripsikan Pendidikan Agama dalam kultur sekolah demokratis sebagai salah satu strategi membumikan deradikalisasi agama di sekolah. Metode penelitian yang digunakan adalah kualitatif naturalistik dengan strategi studi kasus dan mengambil tempat penelitian di SMA Kristen Urimessing Ambon. Objek penelitian ini adalah keseluruhan gejala demokratis dalam proses belajar mengajar Pendidikan Agama Kristen. Hasil penelitian dapat dideskripsikan sebagai berikut, Pendidikan Agama dalam kultur sekolah demokratis berpotensi membumikan deradikalisasi, karena dalam proses belajar mengajar mengoptimalkan sikap kebebasan berpikir kritis, kemandirian, dan akuntabilitas sehingga dapat membentuk keyakinan, sikap dan norma peserta didik untuk: (1) mendalami dan meyakini ajaran agamanya sendiri; (2) berkomitmen mentransformasikan ajaran agamanya secara baik dalam kehidupan pribadi maupun sosial bermasyarakat; dan (3) memberi teladan secara konkret tidak terjebak menggunakan kekerasan dan anarkisme dalam mewujudkan keinginan.